Polyamide resin composition
By adding carbon nanostructures to the semi-aromatic polyamide resin composition, the problems of reduced fluidity and dimensional stability of the molded body after the increase of conductive filler are solved, and excellent mechanical characteristics, heat resistance and anti-static of the molded body are achieved. sex.
Patent Information
- Application Number
- CN202280027662.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-07-20
- Filing Date
- 2022-03-24
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-03-24
AI Technical Summary
After the existing semi-aromatic polyamide resin composition increases the conductive filler, the fluidity, productivity decreases, mechanical characteristics are damaged, dimensional stability decreases, and the dispersion of the conductive filler decreases, resulting in hindering the molded body. question.
By adding carbon nanostructures to the semi-aromatic polyamide containing the reinforcement material, the composition of the resin composition is adjusted so that it contains 40 to 89.8 mass %, 10 to 59 mass % of the reinforcement material and carbon nanostructures. 0.2 to 1.0 mass %.
The polyamide resin composition has excellent fluidity during molding, and a molded body with excellent mechanical properties, heat resistance, dimensional stability, and excellent electrostatic and dust resistance are achieved.
Smart Images

Figure BDA0004485764960000141 
Figure BDA0004485764960000161 
Figure BDA0004485764960000171
Abstract
Description
Technical Field
[0001] The present invention relates to a polyamide resin composition which has excellent fluidity during molding and is suitable for molding precision parts having excellent antistatic properties and dustproof properties. Background Art
[0002] Lens units with imaging elements such as CCD (Charge Coupled Device) and CMOS (Complementary Metal Oxide Semiconductor) are used in mobile phones, game consoles, personal computers, car cameras, mobile phone terminals, etc., and in recent years, the development of more compact and high-performance microlens units has been progressing.
[0003] The lens unit uses reflow soldering to solder the electrical wiring. Therefore, when the precision parts such as the barrel and bracket that constitute the lens unit are exposed to the soldering temperature of the reflow process (up to about 265°C), heat resistance and dimensional stability are required to avoid damaging the appearance. Semi-aromatic polyamides are studied as resin materials for precision parts that meet such required characteristics.
[0004] In addition, the surface of the imaging element and the lens inside the lens unit are prone to black scratches and spots due to dust and dirt, which easily reduces the performance of the camera. Therefore, in order to suppress the adhesion of dust and dirt during manufacturing and use, a scheme of adding conductive fillers to the components constituting the lens unit to impart antistatic properties is being studied. As such conductive fillers, for example, carbon black, carbon nanofibers, graphite, carbon fibers, metal fibers, and metal powders can be cited. For example, Patent Document 1 discloses a polyamide resin composition in which a fibrous reinforcing material and carbon nanofibers are added to a semi-aromatic polyamide.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2016-150992 Summary of the invention
[0008] However, if a semi-aromatic polyamide resin composition containing a certain amount of fibrous reinforcement material is further added with a conductive filler, the fluidity during molding is reduced, and the productivity is reduced. In addition, the mechanical properties of the resulting molded body are impaired, and the conductive filler with a large aspect ratio affects the orientation of the fibrous reinforcement material in the resin composition, which may reduce the dimensional stability of the molded body. Furthermore, if the content of the conductive filler is increased, the dispersibility of the conductive filler is reduced, the conductive filler with a large shape falls off from the cross section of the molded body, and an obstruction occurs in the electronic component part of the lens unit.
[0009] An object of the present invention is to provide a polyamide resin composition which has excellent fluidity during molding and can be formed into a molded product having excellent mechanical properties, heat resistance, and dimensional stability and also excellent antistatic properties and dustproof properties.
[0010] The present inventors have conducted intensive studies to solve the above-mentioned problems and, as a result, have found that the above-mentioned problems can be solved by adding a carbon nanostructure to a semi-aromatic polyamide containing a reinforcing material, thereby completing the present invention.
[0011] The polyamide resin composition of the present invention is characterized by containing 40 to 89.8 mass % of a semi-aromatic polyamide (A), 10 to 59 mass % of a reinforcing material (B), and 0.2 to 1.0 mass % of a carbon nanostructure (C).
[0012] According to the polyamide resin composition of the present invention, the semi-aromatic polyamide (A) is preferably mainly composed of an aromatic dicarboxylic acid component and an aliphatic diamine component, wherein the aromatic dicarboxylic acid component mainly contains terephthalic acid and the aliphatic diamine component mainly contains 1,10-decanediamine.
[0013] According to the polyamide resin composition of the present invention, it is preferred that the semi-aromatic polyamide (A) further contains an aliphatic monocarboxylic acid component having a molecular weight of 140 or more.
[0014] The polyamide resin composition according to the present invention preferably has a volume resistivity of 10 12 Ω·cm or less.
[0015] The polyamide resin composition of the present invention preferably has a half-life of 10 seconds or less.
[0016] The molded article of the present invention is obtained by molding the above-mentioned polyamide resin composition.
[0017] In the molded article of the present invention, it is preferred that the length of the aggregates present on the fracture surface in the longitudinal direction is less than 50 μm.
[0018] The molded article of the present invention is preferably a precision component.
[0019] According to the present invention, there can be provided a polyamide resin composition which has excellent fluidity during molding and can form a molded product having excellent mechanical properties, heat resistance, dimensional stability, and also excellent antistatic properties and dustproof properties.
[0020] The polyamide resin composition of the present invention can be suitably used for molding precision parts such as microlens units. DETAILED DESCRIPTION
[0021] <Polyamide resin composition>
[0022] The polyamide resin composition of the present invention contains a semi-aromatic polyamide (A), a reinforcing material (B) and a carbon nanostructure (C).
[0023] (Semi-aromatic polyamide (A))
[0024] The semi-aromatic polyamide (A) in the polyamide resin composition of the present invention is mainly composed of an aromatic dicarboxylic acid component and an aliphatic diamine component. The content of the aromatic dicarboxylic acid component is preferably 80 mol% or more, more preferably 90 mol% or more, and further preferably 100 mol% in the dicarboxylic acid component. In addition, the content of the aliphatic diamine component is preferably 80 mol% or more, more preferably 90 mol% or more, and further preferably 100 mol% in the diamine component.
[0025] From the viewpoint of obtaining a semi-aromatic polyamide (A) having a particularly excellent balance between melting point and heat resistance, the aromatic dicarboxylic acid component constituting the semi-aromatic polyamide (A) preferably contains terephthalic acid as a main component. The content of terephthalic acid in the aromatic dicarboxylic acid component is preferably 95 mol% or more, more preferably 100 mol%.
[0026] As other aromatic dicarboxylic acid components other than terephthalic acid, isophthalic acid and naphthalene dicarboxylic acid are mentioned, for example.
[0027] Examples of the aliphatic diamine component constituting the semiaromatic polyamide (A) include 1,2-ethylenediamine, 1,3-propylenediamine, 1,4-butylenediamine, 1,5-pentanediamine, 2-methyl-1,5-pentanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 2-methyl-1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, and 1,12-dodecanediamine. One of these may be used alone, or a plurality of them may be used in combination.
[0028] Among them, the aliphatic diamine component preferably contains 1,10-decanediamine as the main component, because a semiaromatic polyamide (A) having a particularly good balance between melting point and heat resistance can be obtained. The content of 1,10-decanediamine in the aliphatic diamine component is preferably 95 mol% or more, more preferably 100 mol%.
[0029] The semi-aromatic polyamide (A) may contain dicarboxylic acids other than aromatic dicarboxylic acids, diamines other than aliphatic diamines, lactams, and ω-aminocarboxylic acids as constituent components unless the effects of the present invention are impaired.
[0030] Examples of dicarboxylic acids other than aromatic dicarboxylic acids include aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, and dodecanedioic acid, and alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid.
[0031] Examples of the diamine other than the aliphatic diamine include alicyclic diamines such as 1,4-cyclohexanediamine and the like, and aromatic diamines such as m-xylylenediamine and p-xylylenediamine.
[0032] Examples of the lactam include caprolactam and laurolactam.
[0033] Examples of the ω-aminocarboxylic acid include aminocaproic acid and 11-aminoundecanoic acid.
[0034] The semi-aromatic polyamide (A) preferably contains an aliphatic monocarboxylic acid component having a molecular weight of 140 or more. Examples of the aliphatic monocarboxylic acid component include stearic acid, caprylic acid, nonanoic acid, capric acid, lauric acid, myristic acid, palmitic acid, and behenic acid. Among them, stearic acid is more preferred in view of its high versatility. The semi-aromatic polyamide (A) contains an aliphatic monocarboxylic acid having a molecular weight of 140 or more, thereby improving the dispersibility of the carbon nanostructure (C) in the resin composition and improving the antistatic property. In addition, the obtained molded body has improved sliding properties, thereby being able to suppress the generation of dust such as wear powder caused by contact and sliding with other parts. The molecular weight of the aliphatic monocarboxylic acid is set to the molecular weight of the aliphatic monocarboxylic acid of the raw material used during polymerization. The content of the aliphatic monocarboxylic acid component is preferably 0.6 to 5.0 mol %, and more preferably 1.0 to 3.5 mol %, relative to all monomers constituting the semi-aromatic polyamide (A).
[0035] The semi-aromatic polyamide (A) may contain a monocarboxylic acid other than an aliphatic monocarboxylic acid unless the effect of the present invention is impaired. Examples of the monocarboxylic acid other than an aliphatic monocarboxylic acid include alicyclic monocarboxylic acids such as 4-ethylcyclohexanecarboxylic acid, 4-hexylcyclohexanecarboxylic acid, and 4-laurylcyclohexanecarboxylic acid, 4-ethylbenzoic acid, 4-hexylbenzoic acid, 4-laurylbenzoic acid, alkylbenzoic acids, and aromatic monocarboxylic acids such as 1-naphthoic acid and 2-naphthoic acid.
[0036] The semi-aromatic polyamide (A) can be produced by a conventionally known heat polymerization method or solution polymerization method. Among them, the heat polymerization method is preferably used from the viewpoint of industrial advantages. As the heat polymerization method, there can be mentioned a method consisting of the following steps: a step (i) of obtaining a reaction product from a dicarboxylic acid component, a diamine component and a monocarboxylic acid component, and a step (ii) of polymerizing the obtained reaction product.
[0037] As step (i), for example, a dicarboxylic acid powder is mixed with a monocarboxylic acid used as needed, and preheated to a temperature above the melting point of the diamine and below the melting point of the dicarboxylic acid, and a method of adding the diamine in a substantially water-free state in a manner that maintains the state of the dicarboxylic acid powder. As another method, a suspension consisting of a molten diamine and a solid dicarboxylic acid is stirred and mixed, and after obtaining a mixed solution, a salt formation reaction caused by the reaction of dicarboxylic acid, diamine and a monocarboxylic acid used as needed, and a formation reaction of oligomers caused by the polymerization of the generated salt are carried out at a temperature lower than the melting point of the semi-aromatic polyamide finally generated, thereby obtaining a mixture of salt and oligomers. In this case, the reaction can be carried out while pulverizing, or it can be temporarily taken out after the reaction and then pulverized. As step (i), the former, which is easy to control the shape of the reaction product, is preferred.
[0038] As step (ii), for example, the reaction product obtained in step (i) is subjected to solid phase polymerization at a temperature lower than the melting point of the semi-aromatic polyamide finally produced to increase the molecular weight to a predetermined molecular weight, thereby obtaining the semi-aromatic polyamide. The solid phase polymerization is preferably carried out at a polymerization temperature of 180 to 270° C., a reaction time of 0.5 to 10 hours, and a stream of an inert gas such as nitrogen.
[0039] The reaction apparatuses for step (i) and step (ii) are not particularly limited, and known apparatuses may be used. Step (i) and step (ii) may be carried out in the same apparatus or in different apparatuses.
[0040] In addition, the heating method in the thermal polymerization method is not particularly limited, and examples thereof include a method of heating the reaction container in a medium such as water, steam, or heat carrier oil, a method of heating the reaction container in an electric heater, and a method of utilizing frictional heat accompanying the movement of the contents such as stirring heat generated by stirring. In addition, these methods may be combined.
[0041] In the production of the semi-aromatic polyamide (A), a polymerization catalyst may be used to improve the efficiency of polymerization. Examples of the polymerization catalyst include phosphoric acid, phosphorous acid, hypophosphorous acid, or salts thereof. The amount of the polymerization catalyst added is preferably 2 mol% or less relative to the total monomers constituting (A).
[0042] In the polyamide resin composition of the present invention, the content of the semi-aromatic polyamide (A) needs to be 40 to 89.8% by mass, preferably 50 to 70% by mass. If the content of the semi-aromatic polyamide (A) exceeds 89.8% by mass, the mechanical strength of the obtained molded body may be reduced. On the other hand, if the content of the semi-aromatic polyamide (A) is less than 40% by mass, the amount of reinforcing material in the resin composition becomes relatively large, and melt kneading sometimes becomes difficult.
[0043] (Reinforcement material (B))
[0044] In order to obtain a molded product having excellent mechanical properties, the polyamide resin composition of the present invention needs to contain a reinforcing material (B).
[0045] Examples of the reinforcing material (B) include fibrous reinforcing materials, plate-like reinforcing materials, and spherical reinforcing materials.
[0046] Examples of fibrous reinforcing materials include carbon fibers, glass fibers, silica fibers, silica / alumina fibers, zirconium oxide fibers, alumina fibers, silicon carbide fibers, metal fibers (stainless steel fibers, alumina fibers, etc.), ceramic fibers, boron whiskers, zinc oxide whiskers, asbestos, wollastonite, potassium titanate whiskers, calcium carbonate whiskers, aluminum borate whiskers, magnesium sulfate whiskers, needle-shaped titanium oxide, sepiolite, xonotlite, milled fibers, cut fibers, and the like.
[0047] Examples of the plate-like reinforcing material include glass flakes, talc, mica, graphite, and metal foil.
[0048] As spherical reinforcement, for example, carbon black, silicon carbide, silicon dioxide, quartz powder, hydrotalcite, fused silica, glasses (glass beads, glass powder, milled glass fiber), carbonates (calcium carbonate, magnesium carbonate, etc.), silicates (calcium silicate, aluminum silicate, kaolin, clay, diatomaceous earth, etc.), metal oxides (iron oxide, titanium oxide, zinc oxide, aluminum oxide, etc.), sulfates (calcium sulfate, barium sulfate, etc.).
[0049] Among them, wollastonite is preferred because it can be densely filled to the end during molding and can exhibit rigidity despite its thin thickness.
[0050] As the reinforcing material (B), one of the above materials may be used alone, or two or more of them may be used in combination.
[0051] The surface of the reinforcing material is preferably treated with a silane coupling agent, a titanium coupling agent, or other high-molecular or low-molecular compound in order to improve dispersibility in the aromatic polyamide (A).
[0052] The content of the reinforcing material (B) in the polyamide resin composition of the present invention needs to be 10 to 59% by mass, preferably 15 to 45% by mass. If the content of the reinforcing material (B) exceeds 59% by mass, the resin composition is sometimes difficult to manufacture particles by melt kneading. On the other hand, if the content of the reinforcing material (B) is less than 10% by mass, the mechanical strength of the molded body obtained is reduced.
[0053] In the present invention, from the perspective of reducing anisotropy and further suppressing dust generation, the average length of the reinforcing material (B) is preferably 250 μm or less. In the present invention, the "average length" of the reinforcing material (B) is the average value of the length of the longest part of the shape of a reinforcing material before being matched with the polyamide resin composition. The lower limit of the average length of the reinforcing material (B) is not particularly limited, but is preferably 0.1 μm from the perspective of raw material handling.
[0054] (Carbon Nanostructure (C))
[0055] In order to obtain a molded body with excellent antistatic properties, the polyamide resin composition of the present invention needs to contain a carbon nanostructure (C). In the present invention, the carbon nanostructure (C) refers to a multilayer carbon nanotube with a cross-linked structure and a branched structure. The carbon nanostructure (C) has a carbon content greater than that of a single-layer or multilayer carbon nanotube, and therefore can impart antistatic properties in a smaller amount. In addition, the carbon nanotube with a branched structure has a high dispersibility during melt mixing, and excellent fluidity during molding of the resin composition, and is not easily left in the form of a coagulant in the molded body.
[0056] The method for producing the carbon nanostructure (C) is not limited, and examples thereof include a chemical vapor deposition method under normal pressure using a roll-to-roll process.
[0057] The content of the carbon nanostructure (C) in the polyamide resin composition of the present invention needs to be 0.2 to 1.0% by mass, preferably 0.3 to 0.8% by mass. If the content of the carbon nanostructure (C) exceeds 1.0% by mass, the antistatic property of the molded body is saturated. On the other hand, if the content of the carbon nanostructure (C) is less than 0.2% by mass, the molded body sometimes does not exhibit antistatic property.
[0058] (Amorphous polyamide)
[0059] The polyamide resin composition of the present invention may also contain amorphous polyamide in order to reduce filler floating of the obtained molded body. The amorphous polyamide used in the present invention refers to a polyamide having a heat of fusion of 1 cal / g or less measured by differential scanning calorimetry (DSC) at a heating rate of 16°C / min in a nitrogen atmosphere.
[0060] The amorphous polyamide resin is obtained by polycondensing at least one diamine and at least one dicarboxylic acid.
[0061] Examples of the diamine include linear or branched aliphatic diamines having 6 to 14 carbon atoms such as 1,6-hexanediamine, 2-methyl-1,5-diaminopentane, 2,2,4-trimethylhexamethylenediamine, 2,4,4-trimethylhexamethylenediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, and 1,12-dodecanediamine; alicyclic diamines having 6 to 22 carbon atoms such as bis(4-aminocyclohexyl)methane, bis(3-methyl-4-aminocyclohexyl)methane, 2,2-bis(3-methyl-4-aminocyclohexyl)propane, p-aminodicyclohexylmethane, isophoronediamine, and 2,6-bis(aminomethyl)norbornane; and aromatic diamines having 8 to 22 carbon atoms such as m-xylylenediamine, p-xylylenediamine, and bis(4-aminophenyl)propane. If necessary, two or more diamines may be used in combination.
[0062] Examples of the dicarboxylic acid include adipic acid, 2,2,4-trimethyladipic acid, 2,4,4-trimethyladipic acid, azelaic acid, sebacic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, and other linear or branched aliphatic dicarboxylic acids having 6 to 22 carbon atoms, cyclohexane-1,4-dicarboxylic acid, 4,4'-dicarboxydicyclohexylmethane, 3,3'-dimethyl-4,4'-dicarboxylic acid, and the like. alicyclic dicarboxylic acids having 6 to 22 carbon atoms such as 4,4'-diphenylmethanedicarboxylic acid, isophthalic acid, tributylisophthalic acid, terephthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, biphenyldicarboxylic acid, diphenyl ether-4,4'-dicarboxylic acid, etc., and aromatic dicarboxylic acids having 8 to 22 carbon atoms such as dicarboxylic acid dicyclohexylmethane, 4,4'-dicarboxylic acid dicyclohexylpropane, and 1,4-bis(carboxymethyl)cyclohexane. If necessary, two or more dicarboxylic acids may be used in combination.
[0063] Examples of commercially available amorphous polyamides include "Grivory G21" manufactured by EMS-CHEMIE Japan, and "RILSAN CLEAR G350", "RILSAN CLEAR G830", "RILSAN CLEAR G850" and "RILSAN CLEAR G170" manufactured by ARKEMA. As the amorphous polyamide, one of the above-mentioned amorphous polyamides may be used alone or two or more thereof may be used in combination.
[0064] The glass transition temperature of the amorphous polyamide is not particularly limited, but is preferably 80 to 200° C., more preferably 110 to 170° C. If the glass transition temperature of the amorphous polyamide is lower than 80° C., the heat resistance of the obtained polyamide resin composition may be significantly reduced.
[0065] When the polyamide resin composition contains amorphous polyamide, the content of the amorphous polyamide is preferably 5 to 20% by mass, more preferably 10 to 15% by mass, based on the semi-aromatic polyamide (A).
[0066] (Acid-modified polyolefin)
[0067] From the viewpoint that the bending elastic modulus of the obtained molded body is reduced and the impact resistance is improved, the polyamide resin composition of the present invention may further contain an acid-modified polyolefin. An acid-modified polyolefin refers to a polyolefin containing an unsaturated carboxylic acid as a monomer component. The content of the unsaturated carboxylic acid is preferably 0.1 to 5% by mass relative to 100% by mass of the acid-modified polyolefin. As acid-modified polyolefins, for example, ethylene / olefin monomers / unsaturated carboxylic acid copolymers and ethylene / aromatic vinyl monomers / diene monomers / unsaturated carboxylic acid copolymers can be cited. As a commercial product of ethylene / olefin monomers / unsaturated carboxylic acid copolymers, for example, "TAFMER MH5020" (maleic anhydride-modified ethylene-1-butene copolymer, manufactured by Mitsui Chemicals, Inc.) can be cited. In addition, as a commercial product of ethylene / aromatic vinyl monomers / diene monomers / unsaturated carboxylic acid copolymers, "TUFTEC M1943" (maleic anhydride-modified styrene-ethylene-butadiene-styrene copolymer (SEBS), manufactured by Asahi Kasei Corporation) can be cited.
[0068] When the polyamide resin composition contains an acid-modified polyolefin, the content of the acid-modified polyolefin is preferably 1% by mass or more, more preferably 5% by mass or more, based on 100% by mass of the semi-aromatic polyamide (A).
[0069] (additive)
[0070] The polyamide resin composition of the present invention may further contain additives such as other fillers, ultraviolet absorbers, light stabilizers, heat stabilizers, antioxidants, plasticizers, mold release agents, lubricants, colorants, antistatic agents, and crystal nucleating agents.
[0071] As other fillers, for example, boron nitride, potassium titanate, magnesium sulfate, asbestos, molybdenum disulfide, phenolic resin particles, cross-linked styrene resin particles, and cross-linked acrylic resin particles can be cited. Other fillers can also be in any form such as powder or cross-shaped. In order to improve the dispersibility in the semi-aromatic polyamide (A), the surface of other fillers is preferably treated with a silane coupling agent, a titanium coupling agent, or other high-molecular or low-molecular compounds.
[0072] As ultraviolet absorbers, for example, benzophenone series, benzotriazole series, and triazine series can be mentioned. As light stabilizers, for example, hindered amine series can be mentioned. As heat stabilizers, for example, phosphorous acid, phosphoric acid, phosphite or their esters, copper compounds, polyols or their esters can be mentioned. As antioxidants, for example, hindered phenol series, sulfur series, phosphorus series, and hindered amine series can be mentioned. As plasticizers, for example, waxes such as polyolefin wax and higher fatty acid esters can be mentioned. As release agents, for example, silicone oil can be mentioned.
[0073] These additives may be used alone or in combination of two or more.
[0074] When the additive is contained, the content thereof is preferably 1% by mass or less of the polyamide resin composition.
[0075] The method for mixing the semi-aromatic polyamide (A), the reinforcing material (B), the carbon nanostructure (C) and the additives used as needed is not particularly limited as long as the effect is not impaired, and a melt-kneading method is more preferred. As a melt-kneading method, for example, a method using a batch kneader such as Brabender, a Banbury mixer, a Henschel mixer, a screw-type rotary machine, a roller, a single-axis extruder, a double-axis extruder, etc. can be cited. The melt-kneading temperature is selected from a region where the semi-aromatic polyamide (A) is melted without decomposing. Usually, the setting temperature of the kneading machine is preferably (Tm) to (Tm+50°C) relative to the melting point (Tm) of the semi-aromatic polyamide (A). However, if the semi-aromatic polyamide (A) is not solidified, it can also be set to (Tm-20°C) to (Tm+50°C). If the set temperature of the kneading machine is higher than (Tm+50°C), the semi-aromatic polyamide (A) may be decomposed, and if the set temperature of the kneading machine is lower than (Tm-20°C), kneading may not be performed.
[0076] (Volume resistivity)
[0077] The polyamide resin composition of the present invention preferably has a volume resistivity of 10 12 Ω·cm or less. If the volume resistivity exceeds 10 12Ω·cm, the composition is an insulator and may not exhibit antistatic properties.
[0078] (half life)
[0079] The polyamide resin composition of the present invention preferably has a half-life of 10 seconds or less. If the half-life exceeds 10 seconds, malfunction of precision parts such as a microlens unit may occur when the composition is charged.
[0080] <Molding body>
[0081] The molded article of the present invention is obtained by molding the polyamide resin composition of the present invention.
[0082] The molding method of the polyamide resin composition is not particularly limited, and examples thereof include injection molding, extrusion molding, blow molding, and sintering molding. Among them, injection molding is preferred from the perspective of the large effect of improving mechanical properties and moldability. The injection molding machine is not particularly limited, and examples thereof include a spiral injection molding machine and a plunger injection molding machine. The polyamide resin composition heated and melted in the cylinder of the injection molding machine is metered at each injection, injected into the mold in a molten state, cooled and solidified into a specified shape, and then taken out of the mold in the form of a molded body. The resin temperature during injection molding is preferably (Tm) to (Tm+50°C). It should be noted that the semi-aromatic polyamide (A), the reinforcing material (B), the carbon nanostructure (C), and the additives used as needed can be melt-kneaded and directly molded, or they can be granulated after melt-kneading to form a mold.
[0083] The molded body of the present invention preferably has a length of less than 50 μm in the long side direction of the agglomerate present on the fracture surface. If the length of the long side direction of the agglomerate is 50 μm or more, it may fall off from the cross section of the molded body. By setting the content of the carbon nanostructure (C) used to 1.0 mass % or less, the length of the long side direction of the agglomerate can be less than 50 μm.
[0084] The molded article of the present invention is excellent in mechanical properties, heat resistance, dimensional stability, antistatic properties and dust resistance, and therefore can be suitably used in precision parts. Specifically, it can be preferably used in microlens units of mobile phones, lens units of vehicle-mounted cameras, infrared cameras, visual auxiliary cameras, image recognition cameras, microscopes, single-lens reflex cameras, binoculars, telescopes, etc., and optical disc drives such as CDs, DVDs, and Blu-ray discs.
[0085] Furthermore, the molded article of the present invention can be used in packages of precision parts, cases for transportation, automobile parts, antenna units for various wireless communications, and sensor detection units for millimeter wave radars.
[0086] Example
[0087] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited thereto.
[0088] 1. Determination method
[0089] (1) Melting point, glass transition temperature
[0090] Using a differential scanning calorimeter DSC-7 manufactured by PERKIN ELMER, the temperature was raised to 350°C at a heating rate of 20°C / min, then maintained at 350°C for 5 minutes, then cooled to 20°C at 100°C / min, maintained at 20°C for 5 minutes, and then further raised to 350°C at 20°C / min (second scan). Then, the peak temperature of the crystal melting peak observed in the second scan was taken as the melting point, and the midpoint of the temperature from the two inflection points of the glass transition was taken as the glass transition temperature.
[0091] (2) Relative viscosity
[0092] The measurement was performed using 96 mass % sulfuric acid as a solvent at a concentration of 1 g / dL and 25°C.
[0093] (3) Tensile strength and tensile elastic modulus
[0094] After the obtained pellets of the polyamide resin composition were fully dried, a multi-purpose test product was produced in accordance with ISO 3167 using an injection molding machine (S-2000i) manufactured by FANUC under the conditions of cylinder temperature (Tm+15°C) and mold temperature (Tm-190°C).
[0095] Using the obtained multi-purpose test product, the tensile strength and tensile elastic modulus were measured in accordance with ISO527-1.
[0096] (4) Load deformation temperature
[0097] Using the multipurpose test piece obtained in the above (3), the load deformation temperature was measured at a load of 1.80 MPa in accordance with ISO75-1 and 2.
[0098] (5) Water absorption
[0099] After the obtained polyamide resin composition pellets are fully dried, a plate-shaped test product of width 60 mm × length 60 mm × thickness 3 mm is produced using an injection molding machine (S-2000i) manufactured by FANUC under the conditions of barrel temperature (Tm+15°C) and mold temperature (Tm-190°C).
[0100] The obtained plate-shaped test product was immersed in distilled water at 23° C. for 24 hours, and the water on the surface was wiped off. Then, the water absorption rate was measured under vaporization conditions at 150° C. using a KARL FISCHER moisture meter manufactured by Mitsubishi Chemical Corporation.
[0101] (6) Molding shrinkage
[0102] The plate-shaped test piece obtained in the above (5) was left standing at 23°C for 24 hours, and then the mold shrinkage before and after the standing was measured.
[0103] In addition, the emission direction is MD, and the direction parallel to the plate surface and perpendicular to the emission direction is TD.
[0104] The test pieces having a mold shrinkage of 1.0% or less in both MD and TD were considered to be acceptable.
[0105] (7) Volume resistivity
[0106] After the obtained polyamide resin composition pellets were fully dried, a circular plate test piece with a diameter of 100 mm and a thickness of 1.6 mm was prepared using an injection molding machine (S-2000i) manufactured by FANUC under the conditions of a cylinder temperature (Tm+15°C) and a mold temperature (Tm-190°C).
[0107] The obtained disk test piece was left to stand at 23°C and 50% RH for 24 hours, and then the volume resistivity was measured in accordance with JIS-K-6911 under the same environment using an electrometer (R8340 manufactured by ADVANTEST) and a RESISTIVITY CHAMBER (R12704A manufactured by ADVANTEST).
[0108] The volume resistivity is 10 12 Test pieces with a value of Ω·cm or less were considered to be acceptable.
[0109] (8) Half-life
[0110] After the obtained polyamide resin composition pellets are fully dried, a plate-shaped test piece of width 40 mm × length 40 mm × thickness 1.6 mm is prepared using an injection molding machine (S-2000i) manufactured by FANUC under the conditions of barrel temperature (Tm+15°C) and mold temperature (Tm-190°C).
[0111] The obtained plate test piece was left to stand at 23°C and 50% RH for 24 hours, and then, under the same environment, a +10kV voltage was applied for 30 seconds using an electrostatic decay tester (Type S-5109 manufactured by SHISHIDO Electrostatics Co., Ltd.) in accordance with JIS-L-1094. The application was then stopped and the turntable was directly rotated while measuring the time it takes for the voltage to decay to 50% of the initial voltage (half-life).
[0112] The test pieces with a half-life of 10 seconds or less were regarded as passing.
[0113] (9) Length of the long side of the condensate
[0114] After the pellets of the obtained polyamide resin composition were fully dried, a flat plate test piece of 20 mm in width × 20 mm in length × 0.5 mm in thickness was prepared using an injection molding machine (S-2000i) manufactured by FANUC under the conditions of a barrel temperature (Tm+15°C) and a mold temperature (Tm-190°C). A mold having a film gate on a surface of 20 mm × 0.5 mm was used.
[0115] The obtained test piece was cut, and the exposed cross section was observed using a microscope (VHX-6000 manufactured by KEYENCE CORPORATION) to confirm the aggregates and measure their size.
[0116] The test pieces with the long side length of the aggregates less than 50 μm were considered to be acceptable.
[0117] (10) Flowability (rod flow length)
[0118] After the pellets of the obtained polyamide resin composition are fully dried, an injection molding machine (J35AD-30H) manufactured by The Japan Steel Works, Ltd. is used to measure the rod flow length under the conditions of barrel temperature (Tm+15°C), mold temperature (Tm-190°C), clamping force of 100 tons, injection pressure of 100 MPa, injection speed of 150 mm / second, and injection time of 5 seconds. A special mold with a single-point gate on one side is installed at the front end of the cylinder. The special mold can be an L-shaped molded body with a thickness of 0.4 mm and a width of 10 mm, with a gate at the upper center of the L shape, and the maximum flow length is 150 mm.
[0119] The rod flow length of the polyamide resin composition is preferably 20 mm or more.
[0120] 2. Raw materials
[0121] The raw materials used in Examples and Comparative Examples are shown below.
[0122] (1) Dicarboxylic acid component
[0123] ·TPA: terephthalic acid
[0124] (2) Diamine component
[0125] ·ODA: 1,8-octanediamine
[0126] ·NDA: 1,9-nonanediamine
[0127] DA: 1,10-decanediamine
[0128] ·DDA: 1,12-dodecanediamine
[0129] (3) Monocarboxylic acid component
[0130] STA: Stearic acid (molecular weight: 284)
[0131] BA: Benzoic acid (molecular weight: 122)
[0132] (4) Polymerization catalyst
[0133] ·SHP: Sodium hypophosphite monohydrate
[0134] (5) Semi-aromatic polyamide
[0135] ·Semi-aromatic polyamide (A-1)
[0136] [Step (i)]
[0137] 4560 parts by mass of TPA powder, 9 parts by mass of SHP, and 490 parts by mass of STA were placed in a ribbon mixer reaction device, and heated to 170°C while stirring at a rotation speed of 30 rpm using a double-screw stirring blade under nitrogen. Then, while maintaining the temperature at 170°C and the rotation speed at 30 rpm, 4950 parts by mass of DA heated to 100°C was continuously added to the TPA powder at a rate of 33 parts by mass / minute over 2.5 hours using a liquid injection device to obtain a reaction product. The molar ratio of the raw material monomers was DA:TPA:STA=49.6:47.4:3.0 (the equivalent ratio of the terminal groups of the raw material monomers was DA:TPA:STA=50.4:48.1:1.5).
[0138] [Step (ii)]
[0139] The reaction product obtained in step (i) was further heated to 230° C. in a reaction apparatus of the ribbon blender used in step (i) under a nitrogen stream and polymerized by heating at 230° C. for 5 hours to obtain a semi-aromatic polyamide (A-1).
[0140] ·Semi-aromatic polyamide (A-2) to (A-5)
[0141] Semi-aromatic polyamides (A-2) to (A-5) were obtained by performing the same operation as in the production of the semi-aromatic polyamide (A-1) except that the resin composition was changed as shown in Table 1.
[0142] Table 1 shows the resin compositions of the semi-aromatic polyamides (A-1) to (A-5) and their property values.
[0143] [Table 1]
[0144]
[0145] (6) Strengthening material (B)
[0146] · SH-1250S manufactured by KINSEIMATEC, wollastonite (aminosilane treated), fiber diameter 8 μm, aspect ratio 15
[0147] (7) Carbon nanostructure (C)
[0148] · CNS ATHLOS100, carbon nanostructure manufactured by CABOT
[0149] (8) Carbon nanotubes
[0150] MWCNT K-NANOs-100T, carbon nanotubes, manufactured by KUMHO, average diameter 8-15nm, average length 26μm
[0151] (9) Amorphous polyamide
[0152] · RILSAN CLEAR G850 manufactured by ARKEMA, heat of fusion 0.26 cal / g, glass transition temperature 147°C
[0153] (10) Acid-modified polyolefins
[0154] MH5020, maleic anhydride-modified ethylene-1-butene copolymer manufactured by Mitsui Chemicals, Inc.
[0155] Example 1
[0156] Using a loss-in-weight continuous quantitative feeder CE-W-1 (manufactured by KUBOTA Co., Ltd.), 59.5 parts by mass of semi-aromatic polyamide (A-1) and 0.5 parts by mass of carbon nanostructure (C) were fed to the main feed port of a co-rotating twin-screw extruder TEM26SS (manufactured by Toshiba Machine Co., Ltd.) with a screw diameter of 26 mm and L / D50, and melt-kneaded. During the process, 40 parts by mass of wollastonite as a reinforcing material (B) was fed from a side feeder and further kneaded.
[0157] After being pulled out from the die into a bundle, it is passed into a water tank for cooling and solidification, and cut with a pelletizer to obtain polyamide resin composition pellets. The barrel temperature of the extruder is set to (melting point of semi-aromatic polyamide + 5°C) to (melting point of semi-aromatic polyamide + 15°C), the screw speed is 250 rpm, and the discharge rate is 25 kg / hour.
[0158] Examples 2 to 11, Comparative Examples 1 to 10
[0159] Polyamide resin composition pellets were obtained by the same operation as in Example 1 except that the composition of the polyamide resin composition was changed as shown in Tables 2 and 3. In Comparative Example 1, melt kneading became difficult due to the large amount of the reinforcing material (B) blended, and pellets could not be obtained.
[0160] Tables 2 and 3 show the compositions and property values of the polyamide resin compositions of Examples 1 to 11 and Comparative Examples 1 to 10.
[0161] [Table 2]
[0162]
[0163] [Table 3]
[0164]
[0165] Since the polyamide resin compositions of Examples 1 to 11 satisfy the requirements of the present invention, the tensile strength, tensile elastic modulus, and load deformation temperature are high, and the molding shrinkage is small. In addition, the volume resistivity as an index of antistatic property is low and the half-life is short, and for the coagulation as an index of dustproof property, no coagulation having a length of 50 μm or more in the long side direction is confirmed.
[0166] The polyamide resin composition of Comparative Example 2 has low tensile strength because the amount of reinforcing material blended is less than the amount specified in the present invention.
[0167] In the polyamide resin composition of Comparative Example 3, since the amount of the carbon nanostructure blended was larger than the amount specified in the present invention, aggregates having a length of 50 μm or more were present.
[0168] Since the amount of the carbon nanostructure compounded in the polyamide resin composition of Comparative Example 4 is smaller than the amount specified in the present invention, the volume resistivity is large and the half-life is long.
[0169] From the comparison of the polyamide resin compositions of Examples 1 to 5 and Comparative Examples 5 to 7 and 9 to 10, it can be seen that even if the amount of conductive material is the same, compared with the use of carbon nanotubes, the rod flow length of the carbon nanostructure is longer, the fluidity during molding is excellent, the volume resistivity of the obtained molded body is small, the half-life is short, and the length of the agglomerate is also small.
Claims
1. A polyamide resin composition, characterized in that Contains 40 to 89.8% by mass of a semi-aromatic polyamide (A), 10 to 59% by mass of a reinforcing material (B), and 0.2 to 1.0% by mass of a carbon nanostructure (C); The carbon nanostructure (C) is a multi-walled carbon nanotube having a cross-linked structure and a branched structure.
2. The polyamide resin composition according to claim 1, characterized in that The semi-aromatic polyamide (A) is mainly composed of an aromatic dicarboxylic acid component and an aliphatic diamine component. The aromatic dicarboxylic acid component mainly contains terephthalic acid, and the aliphatic diamine component mainly contains 1,10-decanediamine.
3. The polyamide resin composition according to claim 1 or 2, characterized in that The semi-aromatic polyamide (A) further contains an aliphatic monocarboxylic acid component having a molecular weight of 140 or more.
4. The polyamide resin composition according to claim 1 or 2, characterized in that The volume resistivity is 10 12 Ω·cm or less.
5. The polyamide resin composition according to claim 1 or 2, characterized in that: The half-life is less than 10 seconds.
6. A molded body, characterized in that The polyamide resin composition according to any one of claims 1 to 5 is molded.
7. The molded body according to claim 6, characterized in that The length of the aggregates present on the fracture surface in the long-side direction is less than 50 μm.
8. The molded body according to claim 6 or 7, characterized in that It is a precision component.
Citation Information
Patent Citations
Polyamide resin composition
JP2016150992A
Semi-aromatic polyamide resin composition
CN104919001A
Carbon nano tube / polyamide-based composite material as well as preparation method and application thereof
CN111454572A